Positive Solutions Using Bifurcation Techniques for Boundary Value Problems of Fractional Differential Equations - Yansheng Liu (Abstract and Applied Analysis)
This paper is concerned with the existence of positive solutions for a class of boundary value problems of fractional differential equations with parameter. The main tools used here are bifurcation techniques and topological degree theory. Finally, an example is worked out to demonstrate the main result.